Design, Synthesis, and Temperature-Driven Molecular Conformation-Dependent Delayed Fluorescence Characteristics of Dianthrylboron-Based Donor–Acceptor Systems - Pandey, Umesh Pratap; Nandi, Rajendra Prasad; Thilagar, Pakkirisamy (Frontiers in Chemistry, 2020)
We report a simple and novel molecular design strategy to enhance rISC in boron-based donor acceptor systems to achieve improved delayed fluorescence characteristics. Dianthrylboryl ((An)2B-) based aryl aminoboranes 1 (donor: phenothiazine) and 2 (donor: N,N-diphenylamine) were synthesized by a simple one-pot procedure. The energy of the electronic excited states in 1 and 2 were modulated by varying the arylamine donor strength and electronic coupling between D and A moieties. The presence of a large π-system (anthryl moiety) on boron enhances the electronic communication between donor arylamine and acceptor boryl moieties and hence both 1 and 2 exhibit delayed fluorescence characteristics in a broad range of temperatures (80-300 K). Single crystal X-ray analysis and temperature dependent photophysical studies together with theoretical studies were carried out to rationalize the observed intriguing optical signatures of 1 and 2.